2013
DOI: 10.1111/mmi.12136
|View full text |Cite
|
Sign up to set email alerts
|

CsrA activates flhDC expression by protecting flhDC mRNA from RNase E‐mediated cleavage

Abstract: Summary Csr is a conserved global regulatory system that controls expression of several hundred Escherichia coli genes. CsrA protein represses translation of numerous genes by binding to mRNA and inhibiting ribosome access. CsrA also activates gene expression, although an activation mechanism has not been reported. CsrA activates flhDC expression, encoding the master regulator of flagellum biosynthesis and chemotaxis, by stabilizing the mRNA. Computer modeling, gel mobility shift, and footprint analyses identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
181
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(186 citation statements)
references
References 56 publications
(105 reference statements)
5
181
0
Order By: Relevance
“…Yakhnin et al later identified the molecular mechanism of CsrA-mediated activation; CsrA binds to two sites within the flhDC RNA leader, which prevents 5= end-dependent cleavage of this transcript by RNase E (Fig. 2) (47). While effects on translation often cause secondary and ␣-helices depicted as arrows and cylinders, respectively, and amino acid sequence comparisons are shown immediately below.…”
Section: Dynamic Effects Of Csra On Translation Rna Turnover and Trmentioning
confidence: 99%
See 1 more Smart Citation
“…Yakhnin et al later identified the molecular mechanism of CsrA-mediated activation; CsrA binds to two sites within the flhDC RNA leader, which prevents 5= end-dependent cleavage of this transcript by RNase E (Fig. 2) (47). While effects on translation often cause secondary and ␣-helices depicted as arrows and cylinders, respectively, and amino acid sequence comparisons are shown immediately below.…”
Section: Dynamic Effects Of Csra On Translation Rna Turnover and Trmentioning
confidence: 99%
“…(F) E. coli CsrA stabilizes flhDC by preventing endonuclease cleavage by RNase E. (Top) CsrA binds to sites (GGA) present in the single-stranded region of two RNA hairpins located at the 5= end of flhDC (47). CsrA binding prevents 5= end-dependent cleavage by RNase E. (Bottom) In the absence of CsrA, RNase E binds to the 5= monophosphorylated end of flhDC and performs several cleavages that initiate turnover of the transcript (47).…”
Section: Dynamic Effects Of Csra On Translation Rna Turnover and Trmentioning
confidence: 99%
“…CsrA regulates the expression of genes involved in lifestyle transitions. In Escherichia coli, CsrA activates glycolysis and central carbon pathways (7)(8)(9)(10)(11)(12)(13) and motility (14,15). Conversely, it represses gluconeogenesis (7), glycogen biosynthesis (16)(17)(18)(19)(20), biofilm formation (21)(22)(23)(24), the stringent response (25), and expression of genes involved in other stress resistance and stationary-phase processes, e.g., cstA, hfq, cel, sdiA, and nhaR (24,(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…These enzymes have been shown to regulate motility and biofilm formation as well as PgaD expression at the posttranscriptional level by altering cyclic di-GMP (c-di-GMP) levels (Jonas et al 2008;Boehm et al 2009;Steiner et al 2013). CsrA also binds the flhD 59 UTR and activates expression of this transcription regulator through protection from cleavage by RNase E (Yakhnin et al 2013). Additional CsrA-mediated effects on biofilm formation might be due to observed CsrA repression of Hfq expression (Baker et al 2007), which could alter the stabilities of sRNA regulators of biofilm formation.…”
mentioning
confidence: 99%